Enhanced anticancer potency of Aloe vera in combination with Royal jelly in non-small cell lung cancer and colorectal adenocarcinoma (Annals of Medical Research, 2023)
Aim: The aim of this study was to determine the anticancer activity of royal jelly (RJ) and Aloe vera (AVE) separately and in combination on human non-small cell lung cancer (A549) and colorectal adenocarcinoma cells (HT29) and to investigate whether the side effects of AVE can be ameliorated by RJ.Materials and Methods: The antiproliferative activity of RJ, AVE, and the combination of AVE and RJ was performed in vitro on A549 and HT29 cells using a Real-Time Cell Analyzer (xCELLigence). To determine the mechanisms underlying the antiproliferative activity, cell apoptosis was performed by flow cytometry using the annexin V-FITC/PI apoptosis detection kit, while cell migration was determined by wound healing assay.Results: Treatment with varying concentrations of AVE, RJ, and the combination of AVE and RJ was concluded to have dose-dependent antiproliferative activity and that the AVE-RJ combination induced 41% of HT29 and 11.79% of A549 early apoptosis (p
Keywords: Aloe vera; Colorectal adenocarcinoma; Non-small cell lung cancer; Royal jelly; Wound healing assay; Real-time cell analyzer/xCELLigence